Congenital pit of the optic nerve head with maculopathy – a case report - Poppe, Ewa; Sajkowska, Marzena; Bandzul, Krzysztof (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
The aim of the article is to present the case of a fifty years old man suffering from congenital pit of the optic head with remission confirmed by OCT examination. The diagnosis was established after indirect ophtalmoscopy and OCT. Congenital pit of the head is a rare anomaly caused by the mutation of a PAX 2 gene. Location of the pathology and its symptoms cause difficulties in diagnosis and may indicate central serous choroidoretinopathy or glaucoma. Modern and non-invasive techniques show a two-layer structure at the edge of corpus vitreum and retina. Confirmation of congenital pit of the optic head has a prognostic value with other diseases of retina, such as hole of macula. Only 25% of cases have symptoms of remission without treatment. The rest require further monitoring and various methods of treatment, including vitrectomy.